2016
DOI: 10.1186/s40064-016-3749-1
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal accumulation during the last 30 years in the Karnaphuli River estuary, Chittagong, Bangladesh

Abstract: Heavy metal contamination of aquatic environment has attracted global attention owing to its abundance, persistence, and environmental toxicity, especially in developing countries like Bangladesh. Five heavy metals, namely chromium (Cr), copper (Cu), nickel (Ni), lead (Pb) and zinc (Zn) were investigated in surface and core sediments of the Karnaphuli River (KR) estuary in Chittagong, Bangladesh, in order to reveal the heavy metal contamination history in estuarine sediments and its response to catastrophic ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 35 publications
1
20
3
1
Order By: Relevance
“…Putyrskaya et al (2015) had also observed cases where 210 Pb activity was maximum in subsurface layers for sediment cores collected in Lakes Brienz, Thun, Lucern and Prealpine Lake Meggione of Switzerland. A similar observation had been made by Wang et al (2016) where they assesed sedimentation rate using 210 Pb chronology on Karnaphuli River estuary, Chittagong, Bangladesh.…”
Section: Distribution Of Artificial and Natural Radionuclides In Sedisupporting
confidence: 75%
See 2 more Smart Citations
“…Putyrskaya et al (2015) had also observed cases where 210 Pb activity was maximum in subsurface layers for sediment cores collected in Lakes Brienz, Thun, Lucern and Prealpine Lake Meggione of Switzerland. A similar observation had been made by Wang et al (2016) where they assesed sedimentation rate using 210 Pb chronology on Karnaphuli River estuary, Chittagong, Bangladesh.…”
Section: Distribution Of Artificial and Natural Radionuclides In Sedisupporting
confidence: 75%
“…The number of times heavy metal concentration in the sediment exceeded the background concentration was determined using the CF. In calculating the CF, Equation 1 was used as presented by El-Sayed, Moussa, and El-Sabagh (2015) and Wang et al (2016).…”
Section: Pollution Assessment Of Heavy Metal In Sedimentmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decades, Chittagong metropolitan area has experienced a considerable population growth and nowadays comprises of more than 4 million inhabitants. As it occurs in most of the coastal cities of Bangladesh, Chittagong has insufficient water treatment facilities and the effluents from diverse sources are discharged practically raw in the estuary endangering ecosystem and public health (Wang et al, 2016). The lack of safe drinking water and sanitation, and the prevalence of waterborne diseases are key challenges for Chittagong's authorities and stakeholders (Lara et al, 2009).…”
Section: Study Sitementioning
confidence: 99%
“…Kết quả hàm lượng kim loại nặng trong trầm tích sông Đáy khá tương đồng với hàm lượng kim loại nặng trong trầm tích sông Korotoa, Bangladesh (Pb: 36 ÷ 83; Cu: 35 ÷ 118; Cd: 0,26 ÷ 2,8; Cr: 55 ÷ 183 mg/kg trọng lượng khô) [11] hay cửa sông Karnaphuli, Bangladesh (Pb: 23,66 ÷ 25,05; Cu: 20,34 ÷ 33,06; Cr: 77,0 ÷ 99,8 mg/kg trọng lượng khô) [12] Tuy nhiên, hàm lượng kim loại nặng trong trầm tích sông Hindon, Ấn Độ (Pb: 27,56 ÷ 313,57; Cu: 21,7 ÷ 280,33; Cd: 0,29 ÷ 6,29 mg/kg trọng lượng khô) cao hơn nhiều so với hàm lượng các kim loại này tại khu vực hạ lưu sông Đáy. Quá trình công nghiệp hóa và gia tăng dân số nhanh tại lưu vực sông Hindon là nguyên nhân gây ra sự tích lũy kim loại nặng tương đối cao trong trầm tích sông Hindon [13].…”
Section: Phương Pháp đáNh Giá Rủi Ro Sinh Tháiunclassified